REPELLENT ACTIVITY OF Cananga Odorata (YLANG YLANG) INCENSE COMBUSTIBLE TOWARDS Aedes aegypti - , CHEYLSEA YONG VI YEN; , Dr. Budi Mulyaningsih, Apt., MS ([Yogyakarta] : Universitas Gadjah Mada, 2014)
50 years where its principal vector is Aedes aegypti. One of the ways to prevent this disease is by using mosquito repellents. Instead of the synthetic chemical repellents, a safer alternative should be use. Cananga odorata is used as a mosquito repellent in different concentrations against the mosquito in the form of incense combustible. Objective: To know the repellent activity of 0%, 10%, 20%, 40%, and 80% Cananga odorata compare to d-allethrin 0.3% group. Methods: A simple post-test only experimental group design was used. Twenty-five adult female Ae. aegypti aged 2-5 days is tested with 5 different concentrations of Cananga odorata